Disassembly of micelles in nanoscopic space to prepare concentric nanotubes with variable hydrophobic interiors - Das, Chayanika; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Nanotubes with variable hydrophobic interiors were prepared by disassembling anionic micelles in the inner walls of positive charge bearing conjugated polymer nanotubes.

Disassembly of micelles to impart donor and acceptor gradation to enhance organic solar cell efficiency - Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
A transparent, conducting and low surface energy surface was prepared by disassembly of anionic micelles, which altered the orientation of the donor polymer and imparted gradation between the donor and acceptor. This configuration increased the solar cell device efficiency.

Dihedral angle control to improve the charge transport properties of conjugated polymers in organic field effect transistors - Dharmapurikar, Satej S.; Chithiravel, Sundaresan; Mane, Manoj V.; Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Chemical Physics Letters, 2018)
Diketopyrrolopyrrole (DPP) and i-Indigo (i-Ind) are two monomers that are widely explored as active materials in organic field effect transistor and solar cells. These two molecules showed impressive charge carrier mobility due to better packing that are facilitated by quadrupoles. We hypothesized that the copolymers of these monomers would also exhibit high charge carrier mobility. However, we envisioned that the dihedral angle at the connecting point between the monomers will play a crucial role in packing as well as charge transport. To understand the impact of dihedral angle on charge transport, we synthesized three copolymers, wherein the DPP was sandwiched between benzenes, thiophenes and furans. The copolymer of i-Indigo and furan comprising DPP showed a band gap of 1.4 eV with a very high dihedral angle of 179 degrees. The polymer was found to pack better and the coherence length was found to be 112 angstrom. The hole carrier mobility of these polymer was found to be highest among the synthesized polymer i. e. 0.01 cm(2)/vs. The copolymer comprising benzene did not transport hole and electrons. The dihedral angle at the connecting point between i and Indigo and benzene DPP was 143 angstrom, which the packing and consequently charge transport properties. (C) 2018 Elsevier B. V. All rights reserved.

D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene

Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene